Transient dormant monomer states for supramolecular polymers with low dispersity - Krishnendu Jalani (Nature Portfolio, 2020)
Monodisperse and well-defined self-assembled materials can be obtained by fuel-driven temporally controlled supramolecular polymerization via the buffered release of monomers. Here the authors show that a redox-responsive transient dormant state of monomer generated by redox reaction can lead to supramolecular polymers with low dispersity.